2014
DOI: 10.1096/fj.14-255901
|View full text |Cite
|
Sign up to set email alerts
|

Acylcarnitines: potential implications for skeletal muscle insulin resistance

Abstract: Insulin resistance may be linked to incomplete fatty acid b-oxidation and the subsequent increase in acylcarnitine species in different tissues including skeletal muscle. It is not known if acylcarnitines participate in muscle insulin resistance or simply reflect dysregulated metabolism. The aims of this study were to determine whether acylcarnitines can elicit muscle insulin resistance and to better understand the link between incomplete muscle fatty acid b-oxidation, oxidative stress, inflammation, and insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
225
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(238 citation statements)
references
References 45 publications
12
225
1
Order By: Relevance
“…Although typically short‐lived, LCAC accumulate in states of inefficient fatty acid oxidation (FAO), which may be attributed to (1) defects in mitochondrial FAO enzymes or (2) increased FAO relative to tricarboxylic acid (TCA) flux; this leads to a bottleneck of carbon substrates at the TCA cycle 53, 54. Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57. However, we found no correlation between plasma LCAC and IR in this study; this suggests that the observed LCAC elevations were not driven by IR 54, 55, 56, 57.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although typically short‐lived, LCAC accumulate in states of inefficient fatty acid oxidation (FAO), which may be attributed to (1) defects in mitochondrial FAO enzymes or (2) increased FAO relative to tricarboxylic acid (TCA) flux; this leads to a bottleneck of carbon substrates at the TCA cycle 53, 54. Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57. However, we found no correlation between plasma LCAC and IR in this study; this suggests that the observed LCAC elevations were not driven by IR 54, 55, 56, 57.…”
Section: Discussionmentioning
confidence: 99%
“…Such defects can be caused or exacerbated by IR, which has, in turn, been associated with elevations in plasma LCAC 54, 55, 56, 57. However, we found no correlation between plasma LCAC and IR in this study; this suggests that the observed LCAC elevations were not driven by IR 54, 55, 56, 57. Regardless of the precise cause, LCAC are transported out to the plasma, where they are subsequently metabolized in several tissues (especially skeletal muscle, liver, and heart) or excreted in urine or bile 52, 56, 57.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations